Forced change: Talking trauma — how journalism educators are finding new ways to teach an age-old topic - Matthew Pearson; Saranaz Barforoush; Duncan McCue; Kelly Roche (Facts & Frictions)
What does a “trauma-informed journalist” look like? What are the specific competencies associated with being a trauma-informed journalist? And what are the metrics used to measure the efficacy of current training on trauma-informed approaches to reporting? These questions grow out of a discussion at the Taking Care Roundtable, which brought newsroom leaders, journalism educators, working journalists, union representatives, and other stakeholders together in Ottawa in October 2022 for a two-day meeting intended to surface practical and innovative solutions to address some of the challenges highlighted in Matthew Pearson’s and David Seglins’s (2022) Taking Care: A report on mental health, well-being and trauma among Canadian media workers. This podcast episode features a discussion among journalism educators about the importance of teaching trauma-informed approaches to reporting, the current gaps in pedagogy and practice, and reflections on the student-led demand for this content in a post-pandemic environment where mental health and well-being is top of mind among many young journalists in training.